1993
DOI: 10.1111/j.1464-410x.1993.tb16186.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse of the Urethral Mucosa in Prepubertal West Indian Girls

Abstract: Forty-two cases of urethral mucosal prolapse were reviewed in Trinidad, West Indies. The main presenting symptom was vaginal bleeding; 31% of patients had associated infection and 97% belonged to social classes III to V; 33% had conservative management and 67% had surgical treatment. It was concluded that treatment should be medical rather than surgical and it is suggested that this is a disease of the low socio-economic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 11 publications
0
32
2
3
Order By: Relevance
“…[10] The main presenting symptom is vaginal bleeding, [9,11,12,14] as in our experience given in this report. In contrast to the reports by other authors, [15] none of our patients presented with acute urine retention. Diagnosis was achieved by physical examination that revealed a soft mass tissue that bleeds on touch.…”
Section: Discussioncontrasting
confidence: 84%
“…[10] The main presenting symptom is vaginal bleeding, [9,11,12,14] as in our experience given in this report. In contrast to the reports by other authors, [15] none of our patients presented with acute urine retention. Diagnosis was achieved by physical examination that revealed a soft mass tissue that bleeds on touch.…”
Section: Discussioncontrasting
confidence: 84%
“…Its occurrence has been postulated to be related to estrogen deficiency and increased intra-abdominal pressure [1]. Poor hygiene and urinary infection may contribute to the development of the disease [3]. Also, supporting this concept is the finding that when urethral prolapse occurs in the postmenopausal age, the presentation is one of the severe urinary symptoms.…”
Section: Discussionmentioning
confidence: 95%
“…The ideal regimen is a combination of sitz baths and topical estrogen and antibiotics. 6 Nonsurgical treatment may reduce the severity of urethral mucosa prolapse, but the recurrence rate may be as high as 67%. 7 It has been suggested that while treatment with topical estrogen has effected cures in children, adult women usually require surgery.…”
Section: Discussionmentioning
confidence: 99%